Early statin use might reduce the hemorrhagic transformation among acute ischemic stroke patients with recanalization therapy: a retrospective cohort study - Pan, Boyan; Lan, Jiaying; Li, Xiaojun; Chen, Haoxuan; Weng, Luankun; Xu, Haoyou; Zhao, Yuanqi; Zhao, Min (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the relationship between early statin administration and hemorrhagic transformation (HT) in patients with acute ischemic stroke (AIS) patients following recanalization therapy.MethodsThis retrospective study included AIS patients who underwent recanalization therapy (intravenous thrombolysis, endovascular treatment, or a combination of both) and categorized them into two groups based on whether statins were administered within 24 h of recanalization therapy. The primary outcome was the occurrence of HT during hospitalization. Secondary outcomes included in-hospital mortality, favorable clinical outcomes (mRS 0–2) at discharge, and neurological improvement 7 ± 2 days post-stroke (defined as a reduction of ≥4 points in NIHSS from baseline).ResultsA total of 266 AIS patients were analyzed, with 164 (61.7%) receiving statins within 24 h (24 h-statins group). The 24 h-statins group demonstrated a significantly lower risk of HT compared to the non-24 h-statins group (4.9% vs. 21.6%, p < 0.001). In-hospital mortality was also lower in the 24 h-statins group, although not statistically significant (4.9% vs. 10.8%, p = 0.076). Favorable clinical outcomes were more frequent in the 24 h-statins group than in the non-24 h-statins group (60.5% vs. 36.7%, p < 0.001). Furthermore, a greater proportion of patients in the 24 h-statins group showed neurological improvement (51.8% vs. 35.1%, p = 0.019). Adjusted multivariate analysis revealed that early statin use was independently associated with a reduced risk of HT (OR 0.16, 95% CI 0.06–0.49, p < 0.001), as well as a positive association with favorable clinical outcomes (OR 3.63, 95% CI 1.42–9.28, p = 0.007) and neurological improvement (OR 5.23, 95% CI 1.96–13.91, p < 0.001). Subgroup analysis indicated that among patients with elevated low-density lipoprotein (LDL) levels, early statin therapy was linked to a lower risk of HT (P for interaction = 0.018).ConclusionEarly statin administration within 24 h of recanalization therapy, in AIS patients was associated with reduced risk of HT and improved neurological outcomes. For patients with elevated LDL levels, early statin therapy may further decrease the risk of HT.